A gestão dos stakeholders na implementação de inovação em serviços no varejo farmacêutico brasileiro - Charotta, Teresa Cristina Alves (2017)
The research question that guided this dissertation was how does the management of stakeholders contribute to the implementation of innovations in services? Thus, the general objective of the dissertation was to understand how the positioning and the relationship of the stakeholders guide the strategies of implementation of innovations in services. In order to do so, it was analyzed, as research object, the implementation of innovation in services in the Brazilian pharmaceutical retail. A descriptive exploratory qualitative research was conducted with a single case study method with intracausal analysis of the Pague Menos Pharmacies Network, with structured field interviews and the Focus Group. Next, it was categorized for Stakeholder analysis: Strategy of Positioning and Relationship Approach to carry out the data collection. In the first. In the data collection stage, field interviews were conducted with highlevel hierarchical stakeholders, CEOs, CIOs and specialized managers in the pharmaceutical and health market. A Focus Group was held with consumers who attend pharmacies and drugstores, but are unaware of what differentiated pharmaceutical services are. Participation in the Abrafarma Future Trends 2016 Event provided observational interviews with entity and government (Anvisa). The data collection period occurred between August and November 2016. As an academic contribution, what was sought in this study was to bring the Stakeholders Theory applied to innovation, service innovation and business model innovation to respond as the stakeholder (Freeman, 1984) and strategic relationship matrix (Frooman, 1999, 2002) that identified the interests, the potential of Power and threat potential of stakeholders. The study was able to demonstrate the strategy adopted by stakeholders the retail network, whether it is supported, partially supported or unsupported. As a managerial contribution, we sought to answer the questions Carrol and Buchholtz (2000) establish for an organization to orient itself in the development of actions with stakeholders.